Pengembangan Alat Ukur Kecerdasan Jamak Siswa Sekolah Dasar Berorientasi Pembelajaran - Darmawan, Nurani Hadnistia; Hilmawan, Hilman (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2019)
The purpose of this research, in general, is to develop measurement tools for verbal-linguistic intelligence, logical-mathematical intelligence, interpersonal intelligence, and kinesthetic intelligence for elementary school students. More specifically the purpose of this study is to test the validity and reliability of measuring tools verbal-linguistic intelligence, logical-mathematical intelligence, interpersonal intelligence, and kinesthetic intelligence of elementary school students. The research method used is descriptive development method. Development of measuring tools for verbal-linguistic intelligence, logical-mathematical intelligence, interpersonal intelligence, and kinesthetic intelligence was collected through survey techniques by observing to see the emergence of each student. Data analysis techniques in this study were conducted by testing the validity and reliability of the measuring instrument. The research subjects were 30 first grade students scattered in SDN 1 Pasirhalang, SDN 1 Selaawi, and SDN 1 Sukaraja, Sukaraja District, Sukabumi Regency in the 2018/2019 school year. The results of this study indicate that the measurement tools for verbal-linguistic intelligence, logical-mathematical intelligence, interpersonal intelligence, and kinesthetic intelligence are in the valid category of 30 indicator items out of 40 indicator items and are reliable with Cronbach's Alpha value of 0.739 which is in the high category.